Profiling of driver mutations in lung adenocarcinoma patients identifies rare compound EGFR mutations sensitive to second-generation EGFR-TKIs - Jun Li; Cuiyun Zhang; Yuping Guan; Siyu Wang; Jiawen Zheng; Junnan Feng; Sile Han; Ruijuan Ma; Pengfei Ren; Shasha Li; Harry J. M. Groen; Klaas Kok; et al. (Holistic Integrative Oncology)
Abstract Background Lung adenocarcinoma (LUAD) is the most predominant histological subtype of lung cancer characterized by driver mutations detected in a substantial proportion of the cases. Tyrosine kinase inhibitors (TKIs) are standard care for the patients with these mutations. In this study, we evaluated the efficiency of an NGS-based 8-gene test in selecting TKIs-sensitive patients in a cohort of treatment-naive Chinese LUAD patients and evaluated the sensitivity of rare compound mutations to different EGFR-TKIs in vitro. Material and methods Targeted sequencing covering the hotspot regions of eight LUAD driver genes was performed across 853 treatment-naive LUAD patients admitted in Henan Cancer Hospital (HNCH cohort). The mutational landscape of HNCH patients was compared with TCGA patients. Logistic regression analysis was used to determine the factors associated with presence of these mutations. Genetically modified LUAD PC9 cells were established to evaluate the sensitivity of selected EGFR rare compound mutations to different EGFR-TKIs. Results A total of 574 single nucleotide variants (SNVs), 270 indels, 88 amplifications, and 87 rearrangements were identified in this study, with EGFR and KRAS being the most frequently mutated genes. Females, mostly life-long non-smokers, had significantly higher EGFR mutation rates than males. Males, primarily smokers, more frequently had KRAS mutations. HNCH patients in general had a higher mutation count than TCGA patients (1.09 vs 0.93 mutations per patient (m/p)), in consistent with its higher proportion of patients with advanced disease. Rare EGFR compound mutations identified in this study, including Exon19del plus L747S/I744V and L858R plus V843I/T854A/G873, conferred genetically modified PC9 cells more sensitive to second-generation EGFR-TKI afatinib in-vivo. Conclusion This NGS-based 8-gene test efficiently identified over 70% of Chinese treatment-naive LUAD patients who are targetable for TKIs. Patients with rare EGFR compound mutations might consider second-generation EGFR-TKIs for treatment.